Adverse childhood experiences and adult mood problems: evidence from a five-decade prospective birth cohort. Issue 14 (4th October 2020) - Selous, Camilla; Kelly-Irving, Michelle; Maughan, Barbara; Eyre, Olga; Rice, Frances; Collishaw, Stephan
Abstract: Background: Retrospectively recalled adverse childhood experiences (ACEs) are associated with adult mood problems, but evidence from prospective population cohorts is limited. The aims of this study were to test links between prospectively ascertained ACEs and adult mood problems up to age 50, to examine the role of child mental health in accounting for observed associations, and to test gender differences in associations. Methods: The National Child Development Study is a UK population cohort of children born in 1958. ACEs were defined using parent or teacher reports of family adversity (parental separation, child taken into care, parental neglect, family mental health service use, alcoholism and criminality) at ages 7–16. Children with no known ( n = 9168), single ( n = 2488) and multiple ( n = 897) ACEs were identified in childhood. Adult mood problems were assessed using the Malaise inventory at ages 23, 33, 42 and 50 years. Associations were examined separately for males and females. Results: Experiencing single or multiple ACEs was associated with increased rates of adult mood problems after adjustment for childhood psychopathology and confounders at birth [2+ v . 0 ACEs – men: age 23: odds ratio (OR) 2.36 (95% confidence interval (CI) 1.7–3.3); age 33: OR 2.40 (1.7–3.4); age 42: OR 1.85 (1.4–2.4); age 50: OR 2.63 (2.0–3.5); women: age 23: OR 2.00 (95% CI 1.5–2.6); age 33: OR 1.81 (1.3–2.5); age 42: OR 1.59 (1.2–2.1); age 50: OR 1.32 (1.0–1.7)]. Conclusions: Children exposed to ACEs are at elevated risk for adult mood problems and a priority for early prevention irrespective of the presence of psychopathology in childhood.